Phytochemical profle and antimicrobial activity of the leaves and stem bark of Symphonia globulifera L.f. and Allophylus abyssinicus (Hochst.) Radlk - Lukubye, Ben; Ajayi, Clement Olusoji; Wangalwa, Rapheal; Rugunda, Grace Kagoro (BMC Complementary Medicine and Therapies, 2022)
Introduction: Symphonia globulifera and Allophylus abyssinicus are used in the management of skin rashes and sores, cough, malaria, digestive diseases, stomach ache, wounds and helminthic infections among others in Uganda, Kenya, Ethiopia, Cameroon. This study aimed at determining the phytochemical profle and antimicrobial activity of these two plants. Methods: The stem bark and leaves of both plants were collected from Bwindi Impenetrable National Park and air-dried under shade at room temperature. Cold maceration, decoction and infusion with methanol, water and ethyl acetate as solvents were used in phytochemical extraction. Preliminary qualitative screening and thin layer chroma tography were used for phytochemical profling. Antimicrobial activity was analysed by agar well difusion assay, broth macro-dilution assay and fractional inhibition concentration index (FICI). Results: The leaves and stem bark of both plants have a diverse set of phytochemical compounds of variable polarity including, tannins, alkaloids, favonoids, saponins, quinones and anthraquinones among others. Generally, methanol and water extracts of S. globulifera and A. abyssinicus had in-vitro bactericidal activity against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa but weak fungistatic activity against Candida albicans. Allophylus abyssinicus leaf water and S. globulifera leaf methanol extract combination had a synergistic activity (ΣFICI=0.37) against S. aureus. Similarly, A. abyssinicus stem bark water extract and A. abyssinicus leaf water extract combination had an addi tive efect (ΣFICI=1) against P. aeruginosa. Conclusion: The leaves and stem bark crude extracts of S. globulifera and A. abyssinicus possess a wide range of bioactive phytochemical compounds but have weak antimicrobial activity against S. aureus, E. coli, P. aeruginosa and C. albicans.
Keywords: Allophylus abyssinicus; Antimicrobial activity; Combination efect; Symphonia globulifera; Phytochemical profle